2013
DOI: 10.1007/s00404-013-2840-x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane expression of TRAIL receptors DR4, DR5, DcR1 and DcR2 in the normal endometrium, atypical endometrial hyperplasia and endometrioid adenocarcinoma: a tissue microarray study

Abstract: PurposeTo evaluate the membrane expression of DR4, DR5, DcR1 and DcR2 in the normal endometrium (NE), atypical endometrial hyperplasia (AEH) and endometrioid adenocarcinoma (EAC).MethodsThe study comprised 197 patients: 20 NE, 18 AEH and 159 EAC. Tissue microarrays were constructed. Membrane expression of DR4, DR5, DcR1 and DcR2 was examined and presented as total score (TS).ResultsIn EAC, the membrane expression of DR4, DR5 and DcR2 was less common compared to NE (p < 0.001; p < 0.001; p = 0.018) and AEH (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…(TRID, TRAIL-R3), DcR2 (TRUNDD, TRAIL-R4), and osteoprotegerin. (Gottwald et al, 2013;Wang & El-Deiry, 2003). Thus, exploring the agents which target the TRAIL-mediated apoptosis pathway has attracted obvious attention in the study field of cancer therapy (Koschny, Walczak, & Ganten, 2007).…”
Section: Ros Role In Crc Treatments Via Extrinsic Death Receptor Pathwaymentioning
confidence: 99%
“…(TRID, TRAIL-R3), DcR2 (TRUNDD, TRAIL-R4), and osteoprotegerin. (Gottwald et al, 2013;Wang & El-Deiry, 2003). Thus, exploring the agents which target the TRAIL-mediated apoptosis pathway has attracted obvious attention in the study field of cancer therapy (Koschny, Walczak, & Ganten, 2007).…”
Section: Ros Role In Crc Treatments Via Extrinsic Death Receptor Pathwaymentioning
confidence: 99%
“…Overexpressed DCR2 is also seen in other human malignancies such as colon cancer and lung cancer [25, 26]. In contrast, Gottwald et al reported DCR2 protein is less common in endometrioid adenocarcinoma compared to normal endometrium [27]. Physiologically, DCR2 is frequently expressed in normal tissues, but often silenced by hypermethylation in a wide range tumour cells including breast cancer, cervical cancer, malignant mesothelioma, neuroblastoma and prostate cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, OPG exhibits strong binding affinity with Receptor activator of NK-kappa-B ligand (RANKL), and plays a prominent role in osteoclastogenesis [28,29]. Contrary to DR4 and DR5 [30,31,32,33], DcR1, DcR2, or OPG have been found to be expressed in normal tissues, but are rarely found in tumor cells [34,35,36].…”
Section: Apoptosis Induced By Trailmentioning
confidence: 99%